Expression of TGF-β/Smads in Cecum and Spleen of Chicken Infected with E. Tenella - Huang,J (2022)
ABSTRACT Chicken coccidiosis is a common and severe parasitic disease caused by infection from Eimeria spp., which affects the integrity of the intestinal mucosa. TGF-β has been shown to play an important role in the healing of intestinal mucosas, immunity, and the maintenance of bowel mucosa integrity. Very little is known about the presence of the components of TGF-β/Smads signaling pathway of chicken at different times following coccidian infection. In the present study, we measured the levels of TGF-β2, 3, 4, receptor TβRI, II, down-stream Smad 2, 3, 7 in cecum and spleen of chicken at different times after inoculation with Eimeria tenella using quantitative real-time PCR. The results showed that the TGF-β/Smads signaling pathway was not activated in cecum in the early stage of infection. However, on the 8th day, the expression of TGF-β2, 4, down-stream protein Smad 2, 7 were significant up-regulated in the spleen, which indicated that the TGF-β/Smads signaling was changed in the E. tenella infection and was differentially expressed in various tissues in the early stages of infection.